Using Google Translate as a Tool in Translating Texts - Budiyanti, Kurnia (Indonesian Journal of Integrated English Language Teaching, 2023)
AbstractGoogle Translate (GT) becomes one of familiar tools used in translation subject. This research investigates the different of using GT on students’ translation tasks and explores the advantages and disadvantages of using GT in translating texts. This research referred to mixed method design. The subjects of the research were 57 students of fourth semester. To collect the data, the researcher used tests and questionnaires. The quantitative data were analysed by using independent sample t-test, while qualitative analysis was used for another data. It was found that there was a significant different in students’ translation results after using Google Translate. Then, from the open-ended questionnaire, it was found that there were advantages of Google Translate such as quick and easy learning, portability and time savings, while the disadvantages were less accurate translation, grammatical structure error and network problem. Thus, it can be concluded that the use of Google Translate was beneficial for translating texts, but the students are suggested to recheck the results for a better translation form.Keywords: Google Translate; tool; translating